2018
DOI: 10.1016/j.jbtep.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

When is experiential avoidance harmful in the moment? Examining global experiential avoidance as a moderator

Abstract: Overall, these results suggest engaging in experiential avoidance in the moment has more negative, immediate effects particularly among those who engage in global, inflexible patterns of experiential avoidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 24 publications
1
16
0
1
Order By: Relevance
“…A second set of models (see Table 4) examined whether between-subjects variability in negative affect (trait negative affect) moderated the association day-to-day to variability in EA with solitary drinking that evening. This was intended to model concepts derived from newer research suggesting EA tends to be most harmful when deployed inflexibly and frequently (e.g., Kashdan et al, 2014;Levin et al, 2018). In other words, it may be more fruitful to examine between subject, trait-like moderators to identify for whom EA is more or less problematic, rather than examining within subject, state-like variables to identify when EA is problematic for all individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A second set of models (see Table 4) examined whether between-subjects variability in negative affect (trait negative affect) moderated the association day-to-day to variability in EA with solitary drinking that evening. This was intended to model concepts derived from newer research suggesting EA tends to be most harmful when deployed inflexibly and frequently (e.g., Kashdan et al, 2014;Levin et al, 2018). In other words, it may be more fruitful to examine between subject, trait-like moderators to identify for whom EA is more or less problematic, rather than examining within subject, state-like variables to identify when EA is problematic for all individuals.…”
Section: Discussionmentioning
confidence: 99%
“…One item assessed a restructuring response to self-critical thoughts ("Overall, I was able to challenge my self-critical thoughts today" [Challenging]) and one item assessed the believability of thoughts, which might be relevant to both restructuring and defusion ("Overall, I didn't believe my self-critical thoughts were true today" [Not believing]. A final item asked about valued action (i.e., personally meaningful actions), "Overall, I was able to do what matters to me today" which was adapted from previous research (Levin, Krafft et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Yet, the effects for daily life openness are promising, given that multiple studies showed that low openness towards aversive mood states and cognitions is associated with reduced wellbeing and other negative outcomes including social anxiety and paranoia (Hershenberg et al, 2017;Levin et al, 2018;Machell et al, 2015;O'Toole et al, 2017;Udachina et al, 2009Udachina et al, , 2014Wenze et al, 2018). That is, low openness towards unwanted experiences may paradoxically exhaust the cognitive and emotional strategies needed to engage effectively in valued activities or important social interactions (Kashdan et al, 2014).…”
Section: Momentary Processesmentioning
confidence: 99%